Pengaruh Karakteristik Wirausaha Dan Orientasi Kewirausahaan Terhadap Keberhasilan Usaha Pada Warung Kelontong Di Kasihan Bantul Yogyakarta - Yati Suhartini (Universitas PGRI Yogyakarta, 2021)
The research was conducted with the aim of knowing the influence of entrepreneurial characteristics and entrepreneurship orientation toward the business success of grocery store in Kasihan Bantul Yogyakarta. The research sample was taken by purposive sampling, amounting 60 people. Data was collected by applying questionnaires,analized by using multiple linier regression,and processed with the SPSS application program. Based on the result of data analysis, it was showed that the two independent variables, namely entrepreneurial characteristics (X1), and entrepreneurship orientation (X2), influenced partially and simultaneously on business success (Y), thus partially or simultaneously supporting the three hypotheses. Based on these results, grocery shop entrepreneurs need to apply smart work, for example online marketingKeywords: entrepreneurial characteristics; entrepreneurship orientation; business success